PENGARUH PENGEMBANGAN PARIWISATA TERHADAP BENTUK KELUARGA MASYARAKAT MATRILINEAL MOSO DI KAMPUNG LUOSHUI, PROVINSI YUNNAN, TIONGKOK - , GE, RUI, Dr. G. R. Lono Lastoro Simatupang, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Moso is a matrilineal ethnic group which has existed thousands of years in the history of China. Big family is the basic unit of Moso society. One Moso family has a dozen members who are all blood related. The oldest women is the leader of the big family. Men and women Moso give birth to babies through Male-leaving Marriges. Children and all the family property inherited by the female members of the family. In traditional society, Moso People live self sufficient by farming, fishing, animal husbandry and trade. With the development of the tourism industry, the tourism industry has replaced traditional industry and is becoming major business in the village named Kampung Luoshui in area Moso . Methodologically, I use structural functionalism in the study. Two basic theory used in this thesis are Industrialization and Familial pattern from William J. Goode and Acculturation Theory in Cultural Adaptation. In this study, I found the change of industrial structure resulting in the changing in social structure in the village Luoshui, Moso matrilineal society. The development of tourism triggers the presence of small families. The collapse of big family which formed Moso society is shaking matrilineal structure Moso.